Numerical and experimental investigation of turbulent n-heptane jet-in-hot-coflow flames. (1st January 2021) - Li, Zhiyi; Evans, Michael J.; Ye, Jingjing; Medwell, Paul R.; Parente, Alessandro
Highlights: A combined numerical and experimental investigation of jet-in-hot-coflow flames with long chain alkanes (n-heptane) is presented. The negative heat release area and absolute value of heat release are increased with decreased coflow oxygen levels. The transitional flame structure, which is observed experimentally, is captured numerically for the low oxygen coflow cases. Flames stabilized in coflows with very low oxygen level demonstrate very gradual increases in OH number density along the axial direction, and lift-off depends on the chosen threshold value of OH number density, whereas cases with higher coflow oxygen level feature clear lift-off heights. Abstract: A turbulent n -heptane jet flame in a jet-in-hot-coflow burner is numerically and experimentally investigated, revealing distinct features of this fuel in a jet-in-hot-coflow burner. The RANS k - ε turbulence model is adopted in combination with a dynamic partially-stirred reactor (PaSR) combustion model. The simulation results are used to support newly-obtained experimental measurements of mean temperature, OH number density and normalised CH2 O-PLIF signal values at several axial locations. The simulations capture the transitional phenomenon observed experimentally for the low coflow oxygen concentration case, which is determined to be due to the two chemical pathways which exist for the n -heptane fuel. The predicted flame weak-to-strong transition heights based on the streamwise (axial) gradient of OH number density show non-monotonic behaviour. Furthermore, an investigation on negative heat release rate region shows that the absolute value of negative heat release rate increases with reduced coflow oxygen content, in contrast to the suppression phenomenon seen in laminar opposed-flow flames.